THE ROLE OF SYNERGETIC PRINCIPLES IN MODERN TRANSLATOLOGY - Alexandra I. Milostivaya (Вестник Северо-Кавказского федерального университета, 2022)
The aim of this article is to observe the epistemic potential of synergetic principles (homeostasis, hierarchy, nonlinearity, openness, instability, dynamic hierarchy, observability) in linguistic translatology.